Cognitive Style of Adolescent Students In Relation to Their Academic Achievement: Exploring the Link Between Cognitive Style and Academic Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In recent years, research in teaching-learning processhas increasingly shifted its emphasis from predictive studies of success andfailure in performance to the understanding of cognitive processes thatunderlie the performance. Prediction of success and failure in academicperformance could be of secondary importance to the insight into the basiccognitive processes that account for either of these terminal behaviours.